Editors' Note: Diet Inflammatory Index and Dementia Incidence: A Population-Based Study. (5th April 2022) - Siegler, James E.; Galetta, Steven
Abstract : Using data from the Hellenic Longitudinal Investigation of Aging and Diet (HELIAD), Charisis et al. evaluated the relationship between the validated diet inflammatory index (DII) and incident dementia. In their cohort of 1, 059 patients, 62 of whom were eventually diagnosed with dementia (5.9% over a mean follow-up of 3 years), there was a strong and independent relationship between DII and eventual dementia diagnosis (HR for each DII point 1.26 [95% CI 1.05–1.52]; p = 0.013). Dr. Daly highlights an important observation regarding this study and similar observational cohorts, noting that these relationships between diet and lifestyle risk factors and later dementia diagnoses often fail to translate into meaningful interventions for at-risk patients. Specifically, there remains no proven benefit of interventions such as reducing inflammatory dietary intake at reducing the long-term risk of dementia. The HELIAD investigators emphasize that the value of their study lies in the potential to design an interventional trial that could leverage these nutritional data, but they acknowledge such a trial may be challenging to conduct.